(NsOC)QÆALXNA PEDAGOGÆKA (B:s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (NpALX^EWSXKIJ(B, (NsTEPAN sERG)QÆJOWI^(B,s)E ((NkI)QÇW (B:s)E (NkONDOR(B,s, 2005)
(Nu POS)QÆBNIKU ROZGLQDA@TXSQ PITANNQ SOCÆALXNO(B-(NPEDAGOGÆ^NOÇ ROBOTI Z L@DXMI RÆZNOWÆKOWIH GRUP TA KATEGORÆJ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NsOC)QÆALXNA PEDAGOGÆKAs)E; (NSOC)QÆALXNA PEDAGOGÆKAs)E; (NSUGESTOLOG)QÆ^NA MAJSTERNÆSTXs)E; (NEKOPSIHOLOG)QÆ^NA SISTEMAs)E; (NSOC)QÆALÆZACÆQs)E; (NMETODIKIs; (NTEHNOLOG)QÆÇs)E; (NTAKTIKIs; (NSOC)QÆALXNIJ PEDAGOGs)E; (Nw)Qæl(B-Æ(NNFÆKOWANÆs)E; (NNARKOZALEVN)QÆs)E; (NPSIHOTROPN)QÆ RE^OWINIs)E; (NRANNQ PROSTITUC)QÆQs)E; (NPEN)QÆTENCÆARNA USTANOWAs)E; (NPENS)QÆONERIs)E; (NBEZDOGLQDN)QÆs)E